Human anatomy &​ physiology - Marieb, Elaine Nicpon (Pearson Education, Inc., 2019)
Unique chapter-opening roadmaps help students keep sight of “big picture” concepts for organizing information; memorable, familiar analogies describe and explain structures and processes clearly and simply; an expanded number of summary tables and Focus Figures help learners focus on important details and processes; and a greater variety and range of self-assessment questions help them actively learn and apply critical thinking skills. To help learners prepare for future careers in health care, Career Connection Videos and Homeostatic Imbalance discussions have been updated, and end-of-chapter Clinical Case Studies have been extensively reworked to include new NCLEX-Style questions.